Liver oligometastatic disease in synchronous metastatic gastric cancer patients: a nationwide population-based cohort study. (January 2023) - Kroese, Tiuri E.; Takahashi, Yuko; Lordick, Florian; van Rossum, Peter S.N.; Ruurda, Jelle P.; Lagarde, Sjoerd M.; van Hillegersberg, Richard; Verhoeven, Rob H.A.; van Laarhoven, Hanneke W.M.
Abstract: Introduction: This population-based cohort study analysed treatment, overall survival (OS), and independent prognostic factors for OS in gastric cancer patients with liver metastases. Methods: Between 2015 and 2017, patients with synchronous metastatic gastric or gastroesophageal junction adenocarcinoma limited to the liver were included from the prospectively maintained population-based Netherlands Cancer Registry. Liver oligometastatic disease (OMD) was defined as ≤3 liver metastases. The primary outcome was OS. Independent prognostic factors for OS were analysed using multivariable Cox regression analysis. Results: A total 295 patients with metastases limited to the liver were included. The primary tumour was resected in four patients (1.4%). Treatment for liver metastases consisted of chemotherapy alone (28.1%), trastuzumab plus chemotherapy (4.7%), surgery (1.0%), or best supportive care (67.5%). Median OS across all included patients was 4.0 months (95% confidence interval [CI]: 3.1–4.5). Liver OMD was detected in 77 patients (26%). Treatment for liver OMD consisted of chemotherapy alone (24.6%), trastuzumab plus chemotherapy (5.2%), surgery (3.9%), or best supportive care (67.5%). Median OS among patients with liver OMD was 5.7 months (95% CI: 4.8–7.5). Across all patients, better OS was independently associated with liver OMD (hazard ratio [HR] 0.66, 95% CI: 0.50–0.87), trastuzumab (HR 0.41, 95% CI: 0.23–0.72) but not with triplet compared with doublet chemotherapy (HR 0.94, 95% CI: 0.57–2.87). Worse OS was independently associated with unknown nodal stage versus cN0 (HR 1.74, 95% CI: 1.17–2.60), diffuse-type versus intestinal-type adenocarcinoma (HR 2.06, 95% CI: 1.32–3.20), and monotherapy or best supportive care versus doublet chemotherapy (HR 1.72, 95% CI: 1.03–2.87, and HR 3.61, 95% CI: 2.55–5.10, respectively). Conclusion: In this population-based cohort study, liver OMD was detected in 26% of patients. Liver OMD and trastuzumab treatment were independently associated with better OS while triplet as compared with doublet chemotherapy was not. OS among patients with liver OMD nevertheless remained poor. The concept of OMD and the benefit of resection of liver OMD may still have been relatively unknown in this disease type during the study inclusion years. Graphical abstract: Image 1 Highlights: 26% of patients with metastatic disease limited to the liver had liver OMD. Liver OMD was independently associated with superior overall survival. Overall survival in patients with liver OMD was nevertheless poor.